Methods for increasing the accuracy of recording the parameters of the cardiovascular system in double-beam photoplethysmography - Y. M. Snizhko; O. O. Boiko; N. P. Botsva; D. V. Chernetchenko; M. M. Milyh (Regulatory Mechanisms in Biosystems, 2018)
Photoplethysmography has recently become more widespread among non-invasive methods for obtaining information on the state of physiological systems of the human body. Serial photoplethysmographs are intended for use in clinics and require special care, therefore, interest in portable media developed on the basis of modern sensors and microcontrollers is growing, which would not only make this method available for individual use, but also expand its capabilities through the use of light of various spectral ranges. Such devices require modified signal processing techniques that allow them to be used in mobile applications. The aim of the work is to develop methods for processing signals from a modern two-beam sensor operating in the red and infrared ranges for the analysis of photoplethysmography on a mobile device (smartphone or tablet). A device using the microcontroller and radio module in the Bluetooth standard allows you to continuously record pulse waves, determine the level of oxygen in the blood, calculate peak-peak intervals and heart rate. The use of the two-beam sensor for registration and the implementation of the developed signal processing methods in the Android operation system application increase the accuracy of setting the maximums on pulse curve and provide a relative error in determining the heart rate and pulse-to-pulse intervals relative to the certified electrocardiograph at 9.2% and 9.6% respectively, with an average level of interference and an average activity. An Android operation system mobile device (tablet, smartphone) allows you to visualize the measurement results, store data in the internal memory, and transfer them to the server for further processing.